MORFOLOGI CERITA RAKYAT MALIND ANIM KANUME (THE MORPHOLOGY OF MALIND ANIM KANUME FOLKTALE) - Esther Rita Embram (Balai Bahasa Sulawesi Utara, 2016)
Yenam Kepala Perang Kanum is the folklore of Malind Anim Kanume, the tribe whose lived in the border zone of Sota Merauke Papua. This research is an effort to document oral literature and to analyze the morphology of Malind Anim Kanume folklore based on Vladimir Propp’s theory. From the analysis, it is known that the folklore were consisted of eleven functions and four spheres of action. The values of this paper are about how to keep the promises and how to work for peace. The important think about the Malind Anim Kanume Sota culture preservation.